Bottom-Up Coarse-Grained Modeling of DNA - Sun, Tiedong; Minhas, Vishal; Korolev, Nikolay; Mirzoev, Alexander; Lyubartsev, Alexander P.; Nordenskiöld, Lars (Frontiers in Molecular Biosciences, 2021)
Recent advances in methodology enable effective coarse-grained modeling of deoxyribonucleic acid (DNA) based on underlying atomistic force field simulations. The so-called bottom-up coarse- graining practice separates fast and slow dynamic processes in molecular systems by averaging out fast degrees of freedom represented by the underlying fine-grained model. The resulting effective potential of interaction includes the contribution from fast degrees of freedom effectively in the form of potential of mean force. The pair-wise additive potential is usually adopted to construct the coarse-grained Hamiltonian for its efficiency in a computer simulation. In this review, we present a few well-developed bottom-up coarse-graining methods, discussing their application in modeling DNA properties such as DNA flexibility (persistence length), conformation, “melting”, and DNA condensation.